Factors That Influence the Value of Companies Listed In Jakarta Islamic Index (JII) in 2013-2016 - Asteria, Beta (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The objectives of this study is to examine the effect of the size of the Board ofCommissioners, the size of the Board of Directors and the Return on Assets (ROA)on the Company Value Listed in Jakarta Islamic Index (JII) in 2013-2016. The datawas obtained from the financial statements published by the Indonesia StockExchange and the annual report of the company. The data was collected by usingpurposive sampling method. The study used panel data, which is a combination oftime series and cross section data. The study used multiple linear regressions. Theresult of the research showed that the independent variable that has significantinfluence to the company value were Board of Directors variable and Return OnAsset (ROA) at significance level of 5%, while the Size of Board ofCommissioner has no significant effect to the value of the companies listed in JII.Research also proved that the size of Board of Directors, the size of Board ofCommissioner and the size of Return On Asset (ROA) simultaneously influence tothe value of the companies listed in JII in 2013-2016 in significant way.Keywords: Size of Board of Commissioners, size of the Board of Directors, Return on Assets(ROA), Company Value